The complexity of DNA damage by radiation follows a Gamma distribution: insights from the Microdosimetric Gamma Model - Bertolet, Alejandro; Chamseddine, Ibrahim; Paganetti, Harald; Schuemann, Jan (Frontiers in Oncology, 2023)
DNA damage is the main predictor of response in radiation therapy for cancer. Its quantification and characterization are paramount for treatment optimization, particularly in advanced modalities such as proton and alpha-targeted therapy. We present a novel approach called the Microdosimetric Gamma Model (MGM) to address this important issue. The MGM uses the theory of microdosimetry, specifically, the mean energy imparted into small sites as a predictor of DNA damage properties. MGM provides the number of DNA damage sites and their complexities, which were found to follow a Gamma distribution. Compared to current methods, the MGM allows for the characterization of DNA damage induced for beams composed of multi-energy components distributed over any time configuration and spatial distribution. The output can be plugged into ad hoc repair models that can predict cell killing, protein recruitments in repair sites, chromosome aberrations, and other biological effects, as opposed to current models solely focusing on cell survival. These features are particularly important in targeted alpha-therapy, for which biological effects remain largely uncertain. The MGM provides a flexible framework to study energy, time, and spatial aspects of ionizing radiation and offers an excellent tool for studying and optimizing the biological effects of these radiotherapy modalities.